Rechtlich-soziale Strukturen und Alltag im Verhältnis zwischen Juden und Christen in der Vormoderne, besonders im Rhein-Main-Neckar-Raum: Eine Einleitung zu vier Fallbeispielen - Battenberg, Friedrich (Aschkenas, 2016)
Scientific research into the early modern development of Jewish Society within a Christian environment has increased considerably in recent years. On the occasion of the Sixteenth World Congress of Jewish Studies in 2013 five young scholars, led by Friedrich Battenberg, presented at the Hebrew University in Jerusalem - in addition to these important lectures - a panel under the heading of »Christian Politics towards Jews in the Region of Frankfurt and Mainz in Early Modern Times«. After a comprehensive introduction the following contribution contains printed versions of two of these lectures (Hausmann and Behr). Verena Kasper-Marienberg changed her subject, because she had to publish her Jerusalem lecture on »Criminal History and Jewish Daily Life« elsewhere. Gabriela Schlick-Bamberger, who spoke in Jerusalem on »Jewish brokers at the Frankfurt exchange«, will publish her contribution as part of her dissertation. Andreas Goeller’s lecture about »Social and Economic Aspects in Jewish Life in Early Modern Germany« will be published in a later number of this journal. Thorsten Burger, who could not participate in the Jerusalem Congress, completed the collection presented here with his relevant contribution on the legislation applied to Jewish affairs by the Frankfurt authorities. The following introduction, as well as the four essays, permit short but profound glimpses into Jewish life conditions in Early Modern Germany.